Analysis of main functional components in different parts of Citrus×aurantium L. Changshanhuyou fruits - YU Dandan; WU Jiaxiong; LIU Ying; WANG Lixia; YANG Xingliang; YE Xingqian; CHEN Shiguo; CHEN Jianle (浙江大学学报. 农业与生命科学版)
In this study, the whole fruit of Citrus×aurantium L. Changshanhuyou was divided into five parts, namely, the flavedo, albedo, segment membrane, juice sacs and seeds, from which polyphenols and pectin polysaccharides were extracted sequentially. Ultra-high performance liquid chromatography-tandem mass spectrometry was used to determine 30 kinds of citrus polyphenols, and the compositions and molecular weights of pectin polysaccharides were compared to comprehensively analyze the compositions of the main functional components in different parts of Citrus×aurantium L. Changshanhuyou fruits. The results showed that flavonoids in various parts mainly existed in flavanones, and the contents of neohesperidin and neoeriocitrin in the albedo were the highest, reaching 13 700.72 μg/g and 6 270.24 μg/g (by dry mass and the same as below), respectively. The contents of cinnamic acids in various parts were higher than that of benzoic acids, and the contents of cinnamic acids in the flavedo were the highest. The yield of pectin polysaccharides extracted from albedo by amylase-assisted ethylenediamine tetraacetic acid solution was the highest (27.46%). The yield of pectin polysaccharides from the flavedo by the extraction of NaOH solution was the highest (11.30%), and the molecular weights (MW) of pectin polysaccharides extracted by the two extraction methods in the flavedo were up to 6.888×105 g/mol and 2.343×105 g/mol, respectively. The flavedo, albedo and segment membrane of Citrus×aurantium L. Changshanhuyou can be used as the main processing sources of flavonoids and pectin, and their rich contents of neoeriocitrins provide new development direction for processing byproducts.